2020
DOI: 10.1039/d0pp00182a
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities to estimate the personal UV radiation exposure from ambient UV radiation measurements

Abstract: People are exposed to solar ultraviolet radiation (UVR) throughout their entire lives. Exposure to UVR is vital but also holds serious risks. The quantification of human UVR exposure is a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…The value of GCF was~0.45 for different parts of the body considered (face and hands) for SZAs corresponding to the selected hypothetical period of exposure. This value stays in agreement with Schmalwieser [36], who showed that parts of the body, which are not horizontally oriented to the sun, receive 20-50% of ambient exposure. Ambient vitamin D 3 dose was estimated from the measured UVI (SM6.5) multiplied by the empirical erythema-vitamin D 3 conversion factor, which was taken from tabular values provided by Czerwińska and Krzyścin [37] and depends on SZA and TCO 3 .…”
Section: Model Estimates Of the Vitamin D 3 Intakesupporting
confidence: 91%
“…The value of GCF was~0.45 for different parts of the body considered (face and hands) for SZAs corresponding to the selected hypothetical period of exposure. This value stays in agreement with Schmalwieser [36], who showed that parts of the body, which are not horizontally oriented to the sun, receive 20-50% of ambient exposure. Ambient vitamin D 3 dose was estimated from the measured UVI (SM6.5) multiplied by the empirical erythema-vitamin D 3 conversion factor, which was taken from tabular values provided by Czerwińska and Krzyścin [37] and depends on SZA and TCO 3 .…”
Section: Model Estimates Of the Vitamin D 3 Intakesupporting
confidence: 91%
“…UVR dose (J/m 2 = W/m 2 × time (s)) received by viable skin is an important factor, and this depends on many biological (e.g., amount of melanin), behavioral (e.g., clothing and sunscreen cover) and environmental factors (e.g., latitude), all of which influence the exposure ratio to ambient (ERTA). This is also dependent on angle of the sun on the body site in question (e.g., horizonal vs. vertical surface) [ 1 ]. Different photobiological endpoints in the skin and eye have different UVR dose thresholds, spectral dependencies and exposure patterns in the case of chronic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The surveys are used to determine average exposure times of selected population groups. Sometimes this information is used to infer the average UV exposure [17,18], but more commonly, the annual UV doses or annual averaged daily UV doses (indicative of chronic UV exposure) have been estimated by integrating ambient UV data over average exposure times [19]. (Sometimes daily doses are computed assuming complete exposure, representing the maximum possible dose [20].)…”
Section: Introductionmentioning
confidence: 99%
“…We build upon the work of survey-based approaches and the smartphone app developed by Morelli et al to ensure that our approach is suitable for use in a smartphone app, while also overcoming many of the limitations of previous works and still circumventing the shortcomings of per-sonal dosimeters. Unlike survey-based approaches, our technique is suitable for analysing both chronic and acute UV exposure and, by utilising ER modelling, our approach can be applied far more generally than that of Morelli et al Recent papers have discussed the core principles of estimating personal doses from ambient UV data and ERs and the promise this approach holds for the future of public health and epidemiology research related to UV exposure [19,34], but this is the first publication to calculate and validate doses using such an approach. Satellite-based personal UV dose estimation can serve as an accessible, low-cost method for accurately estimating UV exposure on a population level, thereby aiding epidemiology research into health outcomes related to UV exposure and public health efforts targeting overexposed or at-risk populations.…”
Section: Introductionmentioning
confidence: 99%